Mapping the Excited‐State Potential Energy Surface of a Photomolecular Motor. Issue 21 (27th April 2018) - Hall, Christopher R.; Browne, Wesley R.; Feringa, Ben L.; Meech, Stephen R.
Abstract: A detailed understanding of the operation and efficiency of unidirectional photomolecular rotary motors is essential for their effective exploitation in molecular nanomachines. Unidirectional motion relies on light‐driven conversion from a stable (1 a ) to a metastable (1 b ) conformation, which then relaxes through a thermally driven helix inversion in the ground state. The excited‐state surface has thus far only been experimentally characterised for 1 a . Here we probe the metastable, 1 b, excited state, utilising ultrafast transient absorption and femtosecond stimulated Raman spectroscopy. These reveal that the "dark" excited‐state intermediate between 1 a and 1 b has a different lifetime and structure depending on the initial ground‐state conformation excited. This suggests that the reaction coordinate connecting 1 a to 1 b differs to that for the reverse photochemical process. The result is contrasted with earlier calculations. Abstract : Starting motors : The excited‐state structure and dynamics in a light‐driven unidirectional rotary motor are shown to be a function of the initial excitation geometry. A detailed understanding of the operation and efficiency of these motors is essential for their effective exploitation in molecular nanomachines.